Les effets sur l’emploi des échanges de produits manufacturés entre pays développés et pays en développement - Balassa, Bela (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
This paper examines prospective changes in employment associated with the expected expansion of trade in manufactured goods between the developed and developing countries over the next decade. It appears that, on balance, the developed countries would experience net employment creation as a result of this trade, and there would be only relatively small decline of employment in their import-substituting industries. In turn, the developing countries would gain employment through increased export that would further contribute to their economic growth, with favorable indirect effects on employment.